PERLINDUNGAN HUKUM BAGI KONSUMEN TERHADAP STANDAR MUTU ALAT UKUR TIMBANGAN PEDAGANG DI PASAR BAWAH BUKITTINGGI - Diva Aurellia; Rika Lestari; Meriza Elpha Darnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
This research is motivated by the existence of problems regarding consumer lossesbecause the scale measuring instrument at Pasar Bawah City of Bukittinggi is not standard.The non-standard measuring instruments for Traders' scales are caused by Traders who donot standardize regularly. Traders also do not provide compensation to consumers becausetraders think that the measuring instruments they have are up to standard. This contradictsArticle 7 letter d with Article 7 letter f of the Consumer Protection Act. Traders are requiredto carry out standardization in order to achieve uniformity of results until quality standardsare met on measuring scales.The method used in this study is a sociological research type, the nature of thisresearch is inductive and the research was conducted at Pasar Bawah Bukittinggi. Thesamples taken in this study were forty-two people. Data collection techniques are byquestionnaires, interviews and literature study. Data analysis uses the concept ofstandardization and law enforcement theory which aims to be an analytical knife in thisstudy, so data analysis is carried out qualitatively, namely data based on sentencedescriptions. Described and concluded with the inductive thinking method by understandingsomething through specific observations and drawing broad conclusions based on theseobservations.The results of this study indicate that the effect of the low legal awareness of tradersand consumers as well as the lack of metrological human resources has caused up to now inPasar Bawah City of Bukittinggi there are still cases of consumer losses due to non-standardmeasuring instruments. Therefore, it is necessary to have the maximal role and efforts of theMetrological UPTD against the deficiencies that occur in the Pasar Bawah City ofBukittinggi by playing an active role in counseling, outreach, monitoring, and taking actionon non-standard measuring instruments. The fulfillment of quality standards for weighingmeasuring instruments has an impact on increasing consumer confidence in these tradersand reducing cases of losses experienced by consumers.Keywords : Consumer Protection, Standardisation, Quality Standards, LawEnforcemen